CREB activity in dopamine D1 receptor expressing neurons regulates cocaine-induced behavioral effects - Bilbao, Ainhoa; Rieker, Claus; Cannella, Nazzareno; Parlato, Rosanna; Golda, Slawomir; Piechota, Marcin; Korostynski, Michal; Engblom, David; Przewlocki, Ryszard; Schütz, Günther; Spanagel, Rainer; Parkitna, Jan R. (Frontiers in Behavioral Neuroscience, 2014)
IIt is suggested that striatal cAMP responsive element binding protein (CREB) regulates sensitivity to psychostimulants. To test the cell-specificity of this hypothesis we examined the effects of a dominant-negative CREB protein variant expressed in dopamine receptor D1 (D1R) neurons on cocaine-induced behaviors. A transgenic mouse strain was generated by pronuclear injection of a BAC-derived transgene harboring the A-CREB sequence under the control of the D1R gene promoter. Compared to wild-type, drug-naïve mutants showed moderate alterations in gene expression, especially a reduction in basal levels of activity-regulated transcripts such as Arc and Egr2. Drug-naïve mutants showed moderate alterations in gene expression, most prominently a reduction in basal levels of activity-regulated transcripts such as Arc and Egr2, when compared to wild-type controls. The behavioral responses to cocaine were elevated in mutant mice. Locomotor activity after acute treatment, psychomotor sensitization after intermittent drug injections and the conditioned locomotion after saline treatment were increased compared to wild-type littermates. Transgenic mice had significantly higher cocaine conditioned place preference, displayed normal extinction of the conditioned preference, but showed an augmented cocaine-seeking response following priming-induced reinstatement. This enhanced cocaine-seeking response was associated with increased levels of activity-regulated transcripts and prodynorphin. The primary reinforcing effects of cocaine were not altered in the mutant mice as they did not differ from wild-type in cocaine self-administration under a fixed ratio schedule at the training dose. Collectively, our data indicate that expression of a dominant-negative CREB variant exclusively in neurons expressing D1R is sufficient to recapitulate the previously reported behavioral phenotypes associated with virally expressed dominant-negative CREB.